PENGARUH MOTIVASI, KOMPETENSI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PERUM BULOG DIVRE JATENG’’ - Della Amanda Sari, 15.05.61.0004; Murdiyanto, Agus (Students' Journal of Economic and Management, 2019)
This study aims to examine and analyze the influence of Motivation, Competence, and Work Environment on the Performance of Employees of Central Java Regional Logistics Bureau. The population in this study is the total number of employees totaling 108 respondents. The data used are primary data, namely data obtained directly from the source. The technique of data collection is done by questionnaire. The analytical method used is the feasibility test of the data, the feasibility test of the model, hypothesis testing using multiple linear regression. Data collected after testing results all data declared valid and reliable. The results showed that motivation had a positive and significant effect on the performance of Central Java Regional Division Bulog employees. Competence has a positive and significant effect on the performance of Central Java Regional Bureau of Logistics Bureau employees. The Work Environment has a positive and significant effect on the performance of Central Java Regional Bureau of Logistics Bureau employees.